Pengaruh Media Kartu Angka Bergambar Terhadap Kecerdasan Logika Matematika pada Taman Kanak-Kanak Mandiri Palembang - Silfani Oktaviani; Mutia Mawardah; Susan Dian Purnamasari; Febriyanti Panjaitan; Evi Yulianingsih; Nia Oktaviani (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Cognitive development in early childhood is a gradual process that requires active learning in the school environment. Teachers, as educational agents, play a crucial role in designing educative interactions and understanding the cognitive development of children. According to Jean Piaget's theory, cognitive development in children continues to evolve until it matches the thinking processes of adults. The Independent Kindergarten Education Foundation in Palembang accommodates children with diverse characteristics. To enhance children's focus and attention, the use of play media, especially picture number cards, is considered an effective learning strategy. This service aims to evaluate the impact of using picture number cards on the development of mathematical logic intelligence in children at the Independent Kindergarten. The service method involves planning, implementation, evaluation, and reporting. The sample consists of 12 children, with 6 in the control group and 5 in the experimental group. The results show a significant improvement in children's logic and mathematics learning activities after the implementation of picture number cards. The average posttest scores indicate an improvement from the pretest, particularly in the experimental group. During the service, children are directly and actively involved, making picture number cards a playful tool that facilitates learning. This service contributes positively to the development of mathematical logic intelligence in Taman Kanak-Mandiri Palembang. The learning strategy using picture number cards can be an effective alternative in providing enjoyable educational services that support children's development